THYROID CRISIS IN A YOUNG WOMAN WITH GESTATIONAL TROPHOBLASTIC DISEASE - Wulandari, Dewi Catur; Dwipayana, I Made Pande; Suastika, Ketut; Budhiarta, AAG; Gotera, Wira; Saraswati, Made Ratna (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Gestational trophoblastic diseases (GTD) include hydatidiform moles to highly malignant choriocarcinoma. Trophoblast produces human chorionic gonadotropin (hCG) which has the same structure as thyrotrophic hormone (TSH) and their receptors. The high level of hCG may induce secondary hyperthyroidism and thyroid crisis. CASE A 27-year-old pregnant woman with vaginal bleeding consulted at the Obstetric and Gynecology Department. She was tachypneic, tachycardic and febrile. She had history of hydatidiform moles twice. She denied having symptoms of hyperthyroidism before. Laboratory exams were leucocyte 18.700, TSH <0,01 µIU/mL, FT4 34,80 ng/ dl, βhCG >1,125,000 mIU/mL. Burch Wartofsky score was highly suggestive of thyroid crisis. She was planned to be given prophyltiouracil and lugol, but these were not available. She got thiamazole 20 mg tid, propanolol 40 mg tid, hydrocortisone 100 mg i.v every 12 h, ceftriaxon 2 gram every 24 h. She immediately underwent curettage. Histopathology showed choriocarcinoma and she was planned to be given chemotherapy. CONCLUSION Thyroid storm is a rare endocrine emergency. One of the related conditions is GTD. Delays in diagnosis and misdiagnosis still contribute to morbidity and mortality.